A national training course for clinical trainers in family medicine - Hanneke Brits (AOSIS, 2024)
Quality vocational training is important to ensure that family physicians can strengthen the district health system. Competent clinical trainers and supervisors, with the necessary educational knowledge and skills, are required for this job. In 2014, a formal Train the Clinical Trainer (TCT) course was introduced in South Africa as a collaborative effort between the Royal College of General Practitioners (RCGP) and the South African Academy of Family Physicians (SAAFPs). To make the training relevant, the course was aligned with the National Unit Standards for Family Medicine, as these defined the learning outcomes for registrars. The aim of the TCT course was to equip workplace-based clinical trainers with an essential set of educational skills, which could be further developed through mentoring and support. Accredited trainers present the face-to-face course yearly to two family physicians from each of the nine departments of family medicine in South Africa. The TCT course is built around the educational principles of learner-centredness and andragogy. During these 5 days of training the roles and responsibilities of trainers and learners, the learning environment, alignment with the curriculum, assessment for and of learning, and leadership are covered. Recently online assessment, the e-portfolio and the use of entrustable professional activities were added to the course content. In the future we would like to accredit more clinical trainers through a process of workplace-based self-evaluation and 360-degree feedback from peers and students. Lastly, we want to expand the training course in the African region. Contribution: The Train the Clinical Trainer (TCT) course, established in 2014 through RCGP and SAAFP collaboration in South Africa, ensures family physicians have essential educational skills. Aligned with national standards, the course embraces learner-centered principles. Ongoing enhancements include online assessments and future plans involve accrediting more trainers through self-evaluation and expanding across the African region.